The Effectiveness of Acceptance and Commitment Therapy on Anxiety, Depression, and Physical Symptoms among Patients with Chronic Pain - Minoo Gueserse; Alireza Zali; Saeed Hassanzadeh; Mohammad Hatami; Morvarid Ahadi (Shahid Beheshti University of Medical Sciences, 2021)
Background and Objective: Chronic pain is among the most common causes of referring to primary medical care centers. The aim of this study was to determine the effectiveness of acceptance and commitment therapy on anxiety, depression, and physical symptoms in patients with chronic pain. Materials and Methods: This study was a quasi-experimental study with pre-test, post-test, follow-up, and a control group. Participants included 60 patients with chronic pain who were referred to medical centers in Tehran in 2019, who were selected in a two steps sampling method. First, a questionnaire was circulated among patients with chronic pain at medical centers who were selected via convenience sampling method. Then, 60 participants were randomly selected from patients who received the highest scores, then randomly assigned to intervention (30 patients) and control (30 patients) groups. Data were collected using the Beck Depression Inventory and Beck Anxiety Inventory. The experimental group received acceptance and commitment therapy in eight sessions of 90 minutes once a week for two months, but the control group did not receive any treatment. Both groups responded to the research questionnaires in three stages: pre-test, post-test, and two-month follow-up. Data analysis was performed using repeated measure ANOVA using SPSS software version 22. Results: The mean (SD) age of participants in the experimental group was 43.7 (8.9) and in the control group 45.2 (9.2). In the experimental group, the mean (SD) depression score decreased from 32.6 (4.4) in the pre-test to 23.2 (5.1) in the post-test, and 22.1 (5.2) follow-up (P<0.001) and the mean (SD) anxiety score decreased from 33.6 (4.9) in the pre-test to 22.6 (4.2) in the post-test and 22.6 (5.1) in follow-up (P<0.001) and the mean (SD) of physical symptoms decreased from 41.5 (3.2) in the pre-test to 33.7 (3.1) in the post-test and 31.8 (3.3) follow-up stages (P<0.001). In the control group, the scores in the three stages of pre-test, post-test and follow-up were not different. Conclusion: Acceptance and commitment therapy was effective in reducing anxiety, depression and physical symptoms in patients with chronic pain.